Pengaruh Implementasi Kebijakan Program Kartu Indonesia Sehat Terhadap Peningkatan Kualitas Pelayanan Kesehatan Masyarakat Di UPTD Puskesmas Pammana Kecamatan Pammana Kabupaten Wajo - Andi Supriadi; Andi Anugrah Aco; Putri Pratiwi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study aims to determine the effect of the implementation of the KIS Program policy on improving the quality of public health services at the UPTD Pammana Health Center, Pammana District, Wajo Regency. The type of research used in this research is survey research, namely a collection of information that is carried out by compiling a list of statements submitted to respondents in the form of a sample from a population, with the main data collection technique being a questionnaire with a quantitative approach method. The results showed that the Policy Implementation of the KIS program at UPTD Pammana Health Center, Pammana District, Wajo Regency, was at an ideal score of 1,089. This generally illustrates that the Policy Implementation of the KIS program at the UPTD Pammana Health Center is in a good category. Meanwhile, the quality of health services at the UPTD Pammana Health Center, Pammana District, Wajo Regency, is at an ideal score of 1,393 which generally illustrates that the quality of health services at the UPTD Pammana Health Center is in the very good category. Overall the implementation of the Healthy Indonesia Card program policy contributed strongly to improving the quality of public health services with a total of r = 0.637. There is a positive and significant influence between the implementation of KIS program policies on improving the quality of health services at the UPTD Pammana Health Center, Pammana District, Wajo Regency.